The Monday Afternoon Tree: A Grounded Theory of Slacktivism among Filipino Students in a State University - Paul Angelo B. Fulleros; Rowell P. Nitafan (Philippine Social Science Journal, 2024)
This grounded theory study explores the emerging worldview of "slacktivism" among Filipino university students, utilizing in-depth interviews and focus group discussions with students active in online activism. Employing Charmaz’s constructivist approach, the research introduces the "Monday Afternoon Tree" model to illustrate the key components of slacktivism: its roots, blooming, and withering. The study finds that various factors motivate slacktivism, leading to both positive and negative consequences. While slacktivism's impact on politics is often minimal and indirect, it can increase political awareness and participation. Future research should employ a sequential exploratory approach to further understand this complex phenomenon and empirically validate its underlying domains.